1985
DOI: 10.1111/j.1755-3768.1985.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous surgery in patients with primary neuropathic amyloidosis

Abstract: Pars plana vitrectomy was performed in 9 patients from the north of Sweden because of amyloid deposits of the vitreous. Operative technique and post-operative results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The results are remarkable, with a marked increase in visual acuity, if no other eye diseases exist 8,11,18 as we could corroborate in our study. However, most authors refer a recurrence after several years of follow-up, with new deposition of amyloid in the vitreous cavity, leading to a decrease in visual acuity and need for a new vitrectomy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results are remarkable, with a marked increase in visual acuity, if no other eye diseases exist 8,11,18 as we could corroborate in our study. However, most authors refer a recurrence after several years of follow-up, with new deposition of amyloid in the vitreous cavity, leading to a decrease in visual acuity and need for a new vitrectomy.…”
Section: Discussionsupporting
confidence: 87%
“…However, most authors refer a recurrence after several years of follow-up, with new deposition of amyloid in the vitreous cavity, leading to a decrease in visual acuity and need for a new vitrectomy. 8,18,[25][26][27][28][29] Results of out study confirmed that vitrectomy is a safe and useful treatment for vitreous opacities in patients with FAP-I. No complications of vitrectomy (retinal detachment, retinal tear, cataract, and glaucoma) were observed.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The symptoms presented by patients are floaters and, later, decreased vision. The clinical course and the results of vitrectomy have been subject to numerous reports (Sandgren et al. 1985; Doft et al.…”
Section: Discussionmentioning
confidence: 99%
“…Vitreous veils typically occur in FAP patients as ‘glass wool’ opacifications and usually cause only marginal visual impairment. The vitreous veils probably represent transthyretin deposits synthesised by the retinal pigment epithelium and visual acuity usually returns to normal when clear imaging conditions are restored by vitrectomy 7. In our patient, the unilateral vitreous opacities (figure 1C), could not explain the complete loss of light perception, and vitrectomy was not performed.…”
Section: Discussionmentioning
confidence: 61%